2019
DOI: 10.1051/0004-6361/201834416
|View full text |Cite
|
Sign up to set email alerts
|

Complex molecular gas kinematics in the inner 5 kpc of 4C12.50 as seen by ALMA

Abstract: The nearby system 4C12.50, also known as IRAS 13451+1217 and PKS 1345+12, is a merger of gas-rich galaxies with infrared and radio activity. It has a perturbed interstellar medium (ISM) and a dense configuration of gas and dust around the nucleus. The radio emission at small (∼100 pc) and large (∼100 kpc) scales, as well as the large X-ray cavity in which the system is embedded, are indicative of a jet that could have affected the ISM. We carried out observations of the CO(1-0), (3-2), and (4-3) lines with the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…4.5, we discussed in detail four specific cases (Cen A, IC 5063, NGC 1266, and NGC 1377), but evidence is found for other galaxies with radio jets (e.g. Dasyra and Combes 2012;Guillard et al 2012;Morganti and Oosterloo 2018;Murthy et al 2019;Fotopoulou et al 2019;Zovaro et al 2019;Fernández-Ontiveros et al 2019). It is generally found that the jet-driven outflowing gas in the molecular phase is as massive as the neutral-atomic phase, or even more massive, and largely exceeding the mass in the ionized phase.…”
Section: Molecular Gas Componentmentioning
confidence: 99%
“…4.5, we discussed in detail four specific cases (Cen A, IC 5063, NGC 1266, and NGC 1377), but evidence is found for other galaxies with radio jets (e.g. Dasyra and Combes 2012;Guillard et al 2012;Morganti and Oosterloo 2018;Murthy et al 2019;Fotopoulou et al 2019;Zovaro et al 2019;Fernández-Ontiveros et al 2019). It is generally found that the jet-driven outflowing gas in the molecular phase is as massive as the neutral-atomic phase, or even more massive, and largely exceeding the mass in the ionized phase.…”
Section: Molecular Gas Componentmentioning
confidence: 99%
“…These observations; however, are unable to rule out a more localised impact, which can sometimes be observed using spatially-resolved molecular gas measurements (e.g. Salomé et al 2017;Rosario et al 2018;Fotopoulou et al 2019;Ramakrishnan et al 2019;Shin et al 2019;Lutz et al 2020). Furthermore, we can not rule out that these processes will have an impact on the global molecular gas supply on longer timescales.…”
Section: The Role Of Agn In Galaxy Evolutionmentioning
confidence: 80%
“…Molecular gas outflows traced by CO gas have been identified in both radio and quasar mode AGN (see e.g. Cicone et al 2014;King & Pounds 2015;Morganti et al 2015;Bischetti et al 2019;Fotopoulou et al 2019;Oosterloo et al 2019;Lutz et al 2020;Veilleux et al 2020). However these outflows typically only represent ∼10 per cent of the molecular gas luminosity (see e.g.…”
mentioning
confidence: 99%
“…In Section 4.5, we discussed in detail four specific cases (Cen A, IC 5063, NGC 1266, and NGC 1377), but evidence is found for other galaxies with radio jets (e.g. Dasyra and Combes 2012;Guillard et al 2012;Morganti and Oosterloo 2018;Murthy et al 2019;Fotopoulou et al 2019;Zovaro et al 2019;Fernández-Ontiveros et al 2019). It is generally found that the jet-driven outflowing gas in the molecular phase is as massive as the neutral-atomic phase, or even more massive, and largely exceeding the mass in the ionized phase.…”
Section: Molecular Gas Componentmentioning
confidence: 99%